Disruptions in Liver Function among Cancer Patients and Patients Treated with Tyrosine Kinase Inhibiting Drugs: Comparisons of Two Population-Based Databases. (21st April 2013) - Landis, Sarah H.; Nordstrom, Beth L.; Sansbury, Leah B.; Shantakumar, Sumitra; Laurent, Samantha A. St.; Fraeman, Kathy H.; Nelson, Jeanenne J.
Abstract : Liver toxicity is a recognized adverse event associated with small molecule tyrosine kinase inhibitors (TKIs). Electronic Medical Record (EMR) databases offer the most precise data to investigate the rate of liver function test (LFT) elevations; however, they can be limited in sample size and costly to access and analyze. Health insurance claims databases often contain larger samples sizes but may lack key health information. We evaluated the feasibility of utilizing a large claims database to calculate incidence rates (IRs) of LFT elevations among a general cohort of cancer patients and a cohort of patients treated with TKIs by comparing the results to a "gold standard" oncology-specific EMR database. IRs for the TKI cohorts were very similar between the two databases; however, IRs were higher in the EMR database for the cancer cohorts. Possible explanations for these differences include lack of specificity when defining a cancer case, poor capture of laboratory data, or inaccurate assessment of person-time in the insurance claims database. This study suggests that insurance claims data may provide reliable results when investigating liver toxicities associated with oncology drug exposure; however, there are limitations when assessing laboratory outcomes for cohorts defined solely by disease status.